Formulation and Characterization of Gabapentin Microcapsule - Parveen, Reshma; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The goal of the current study was to develop and characterize Gabapentin-loaded microcapsules by the ionotropic gelation process for the creation of a sustained-release oral drug delivery system. Gabapentin, an antiepileptic medication utilized to treat epilepsy and neuropathic pain, has the pharmacokinetic disadvantages of a low biological half-life, non-linear absorption, and dosing frequency. To overcome such limitations, a new encapsulation approach with sodium alginate as a major polymer and calcium chloride as a cross-linker was adopted. Chitosan was also used as a secondary polymer for coating in order to improve mucoadhesion and extend residence time in the gastrointestinal tract. Different formulations were made in different concentrations of sodium alginate (2%, 3%, and 4% w/v) and in drug-to-polymer ratios (1:1 and 1:2). The microcapsules were tested for micromeritic characteristics, particle size distribution, encapsulation efficiency, drug content, swelling index, surface pH, and in vitro drug release. The optimized batch had superior flow characteristics, spherical morphology, and excellent encapsulation efficiency of over 85%. The particle size was increased by polymer concentration and coating. Sustained release for up to 8 hours, according to Higuchi and Korsmeyer-Peppas kinetic models, was shown in in vitro drug release studies in phosphate buffer (pH 6.8), representing diffusion-controlled and anomalous transport mechanisms. Stability studies performed according to ICH Q1A(R2) guidelines under both long-term (25°C/60% RH) and accelerated (40°C/75% RH) storage conditions for 3 months assured the physicochemical stability of the optimized dosage form. There were no remarkable differences in pH, viscosity, drug content, or sterility. The results indicate that Gabapentin microcapsules prepared by ionotropic gelation show a promising alternative to traditional dosage forms by enhancing bioavailability, decreasing the frequency of dosing, and increasing patient compliance.